HUBUNGAN TINGKAT PENGETAHUAN DAN PARITAS DENGAN KEPATUHAN KUNJUNGAN ANC PERTAMA PADA IBU HAMIL DI PUSKESMAS JUWANGI - Siti Agustina; Titik Wijayanti; Triani Yuliastanti (Jurnal Komunikasi Kesehatan, 2026)
Achievements visit antenatal care first (K1) in the District Juwangi in 2025 was 87%, still is below the national target of ≥95 %. Compliance Mother pregnant in do first ANC visit influenced by various factors , including level knowledge And parity . Study This aim know connection level knowledge And parity with compliance first ANC visit on Mother pregnant at the Community Health Center Fragrant . Study use method quantitative with design cross sectional . Population study is all over Mother pregnant in the area Work Community Health Center Juwangi on April 2026. Sampling technique using quota sampling with amount sample of 30 respondents, respondents are pure K1. Data collection using questionnaire knowledge And sheet observation. The knowledge in questin is knowlwdge about the objectives, benefits, and timing of ANC imlementation. Data analysis using test Chi-Square . Results study show part big respondents own level knowledge not enough as many as 12 respondents (40%), some of them big 27 respondents ( 90 %) were multigravida , and the majority of respondents were compliantwith attending the first antenatal care (ANC) visit before 12 weeks of gestasion according to the standart (pure K1) as many as 16 respondents (53.3%). Results analysis show there is connection significant between level knowledge with compliance first ANC visit with a p-value of 0.000 < 0.05 . No there is connection significant between parity with compliance first ANC visit with a p-value of 0.626 > 0.05 . The conclusion of this study shows a relationship between pregnant women's knowledge and compliance with their first ANC visit. Meanwhile, parity, or the number of deliveries experienced, does not affect the level of pregnant women's compliance with their first ANC visit. Keywords : ANC, compliance, parity, knowledge.